CURRENT TRENDS INNOVATION AND INVESTMENT ENSURING THE DEVELOPMENT OF AN ENVIRONMENTALLY-ORIENTED ECONOMY - TARASOVA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to analyze the state of ecological determinants of the development of the region, to justify the directions and means of the regional policy of transition to an ecologically oriented approach in relation to the development of the economy and the formation of its innovation and investment support. The article points out the relevance of the formation and implementation of the policy of formation of investment and innovation support for the formation and development of an ecologically oriented economy. On the example of the regions of the Carpathian region of Ukraine, key problem areas in terms of ensuring sustainable ecologically-oriented development of the regional economy have been identified. The directions and means of the regional policy of transition to an ecologically oriented type of development of the regional economy have been determined. The toolkit for the formation of innovation and investment support for ecologically oriented development of the region’s economy has been determined. The strategic priorities of the policy of ensuring the development of an ecologically-oriented economy have been determined, namely smart spatial development, increasing the role of green economy sectors, compliance with the principles of consumer safety and social responsibility, strengthening the resistance of the health care system, balancing the labor market and employment of the population, forming a clean and safe life space The purpose of the environmental protection policy is determined, which consists in overcoming the ecological crisis and improving the parameters of the ecological component of the quality of life of the population. Target guidelines for the improvement of the ecological state of the territory have been determined, in particular in terms of preservation and restoration of natural capital, ensuring the cleanliness of air, water and territory, the transition to a green economy, the formation of a model of ecologically appropriate behavior of the population and business entities. The toolkit for the formation of innovation and investment support for ecologically oriented development of the region’s economy has been defined. The scientific novelty of the research results lies in the fact that the methodological and applied provisions of a comprehensive approach to overcoming the ecological crisis and improving the parameters of the development of an ecologically oriented economy are substantiated; the specificity of the approach is the orientation towards the formation of ecologically appropriate behavior - a system of human actions and deeds aimed at preserving, improving, as well as proactive activities to restore the state of the environment.